2013
DOI: 10.6061/clinics/2013(07)17
|View full text |Cite
|
Sign up to set email alerts
|

Lack of reliable clinical predictors to identify obstructive sleep apnea in patients with hypertrophic cardiomyopathy

Abstract: OBJECTIVE:Obstructive sleep apnea is common among patients with hypertrophic cardiomyopathy and may contribute to poor cardiovascular outcomes. However, obstructive sleep apnea is largely unrecognized in this population. We sought to identify the clinical predictors of obstructive sleep apnea among patients with hypertrophic cardiomyopathy.METHODS:Consecutive patients with hypertrophic cardiomyopathy were recruited from a tertiary University Hospital and were evaluated using validated sleep questionnaires (Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Most of the articles were from Brazil (35) 52 57 , 60 , 61 , 63 65 , 70 , 71 , 73 86 , 88 , 91 93 , 95 97 , 99 while the others were from Chile (5) 58 , 68 , 87 , 89 , 94 , Mexico (4) 66 , 67 , 90 , 100 , Peru (3) 62 , 69 , 72 and Argentina (2) 59 , 98 . The most frequently studied patients were those with Obstructive Sleep Apnea - Hypopnea Syndrome (OSAHS) (22) 53 , 54 , 58 – 62 , 64 69 , 74 , 75 , 79 , 81 , 86 , 87 , 90 , 94 , 97 , 98 and obesity (13) 52 , 71 , 73 , 80 , 82 85 , 91 , 92 , 95 , 99 , 100 ; other diseases included HIV/AIDS, sleep disorders, bronchiectasis, depression, stroke, epilepsy, hepatic and cardiovascular pathologies. The instrument or methodology to measure NC was reported in 29 studies 54 57 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…Most of the articles were from Brazil (35) 52 57 , 60 , 61 , 63 65 , 70 , 71 , 73 86 , 88 , 91 93 , 95 97 , 99 while the others were from Chile (5) 58 , 68 , 87 , 89 , 94 , Mexico (4) 66 , 67 , 90 , 100 , Peru (3) 62 , 69 , 72 and Argentina (2) 59 , 98 . The most frequently studied patients were those with Obstructive Sleep Apnea - Hypopnea Syndrome (OSAHS) (22) 53 , 54 , 58 – 62 , 64 69 , 74 , 75 , 79 , 81 , 86 , 87 , 90 , 94 , 97 , 98 and obesity (13) 52 , 71 , 73 , 80 , 82 85 , 91 , 92 , 95 , 99 , 100 ; other diseases included HIV/AIDS, sleep disorders, bronchiectasis, depression, stroke, epilepsy, hepatic and cardiovascular pathologies. The instrument or methodology to measure NC was reported in 29 studies 54 57 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…Several factors may play a role in the under‐recognition of OSA in this specific population. Previous studies showed that patients with cardiac disorders often do not display the usual signs and symptoms of OSA . In addition, there is no formal screening tool for OSA applied as a part of routine management of patients with cardiac arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that patients with cardiac disorders often do not display the usual signs and symptoms of OSA. 36 In addition, there is no formal screening tool for OSA applied as a part of routine management of patients with cardiac arrhythmia. Another general factor is the challenges associated with obtaining PSG, the gold-standard method for diagnosis of OSA.…”
Section: Under-recognition Of Osa In Patients With Afmentioning
confidence: 99%
“…Daytime sleepiness is often the primary reason that patients with insomnia, circadian rhythm disorders, and sleep‐related breathing disorders present for treatment. Nonetheless, it is not always a reliable clinical indicator for identifying OSA . Sleepiness has, however, been found to be an independent risk factor associated with depression …”
Section: Introductionmentioning
confidence: 99%